Component‐resolved microarray analysis of IgE sensitization profiles to Culicoides recombinant allergens in horses with insect bite hypersensitivity. Issue 4 (3rd September 2020) - Novotny, Ella N.; White, Samuel J.; Wilson, A. Douglas; Stefánsdóttir, Sara B.; Tijhaar, Edwin; Jonsdóttir, Sigridur; Frey, Rebekka; Reiche, Dania; Rose, Horst; Rhyner, Claudio; Schüpbach‐Regula, Gertraud; Torsteinsdóttir, Sigurbjörg; et al.
Abstract: Background: Allergy to bites of blood‐sucking insects, including biting midges, can affect both human and veterinary patients. Horses are often suffering from an IgE‐mediated allergic dermatitis caused by bites of midges ( Culicoides spp) . With the aim to improve allergen immunotherapy (AIT), numerous Culicoides allergens have been produced as recombinant (r‐) proteins. This study aimed to test a comprehensive panel of differently expressed Culicoides r‐allergens on a cohort of IBH‐affected and control horses using an allergen microarray. Methods: IgE levels to 27 Culicoides r‐allergens, including 8 previously unpublished allergens, of which 11 were expressed in more than one expression system, were determined in sera from 347 horses. ROC analyses were carried out, cut‐offs selected using a specificity of 95% and seropositivity rates compared between horses affected with insect bite hypersensitivity (IBH) and control horses. The combination of r‐allergens giving the best performing test was determined using logistic regression analysis. Results: Seropositivity was significantly higher in IBH horses compared with controls for 25 r‐allergens. Nine Culicoides r‐allergens were major allergens for IBH with seven of them binding IgE in sera from > 70% of the IBH‐affected horses. Combination of these top seven r‐allergens could diagnose > 90% of IBH‐affected horses with a specificity of > 95%. Correlation between differently expressed r‐allergens was usually high (mean = 0.69, range: 0.28‐0.91). Conclusion: This microarray will be a powerful tool for the development of component‐resolved, patient‐tailored AIT for IBH and could be useful for the study of allergy to biting midges in humans and other species. Abstract : In this study, we identify and produce eight new Culicoides r‐allergens, Cul o 8 to Cul o 15. Out of 27 tested Culicoides r‐allergens, nine are major allergens for IBH and seven bind serum IgE in > 70% of the IBH‐affected horses. Combination of these seven r‐allergens could diagnose > 90% of IBH horses with a specificity > 95%. Abbreviations: IBH, equine insect bite hypersensitivity; r‐allergen/protein, recombinant allergen/protein.